The Impact of varus and valgus alignment on knee cartilage quality assessed by magnetic resonance imaging: insights from the IMI-APPROACH cohort - Bax, Eva A.; Kerkhof, Joost A.J.; van Egmond, Nienke; Kuiper, Ruurd J.A.; Rayegan, Hassan; Kloppenburg, Margreet; Blanco, Francisco J.; Haugen, Ida K.; Berenbaum, Francis; Mastbergen, Simon C.; Eckstein, Felix; Wirth, Wolfgang; et al. (Knee, 2025)
Background: Lower limb malalignment increases the risk of unicompartmental knee osteoarthritis (KOA). This study investigates the association between knee cartilage quality, assessed via MRI-based T2 mapping, and lower limb malalignment. It also examines whether cartilage quality is more influenced by bony or intra-articular malalignment. Methods: In this cross-sectional analysis of 156 knees from the IMI-APPROACH cohort, tibiofemoral cartilage T2 values were measured using high-resolution MRI, distinguishing superficial and deep layers. Malalignment was categorized into entire leg, bony, and intra-articular malalignment (via the Joint Line Convergence Angle). Correlations between T2 values and alignment were assessed using Spearman's rho. A subgroup analysis evaluated cartilage quality in constitutional malalignment (malalignment without intra-articular deviation). Results: Cartilage T2 values were significantly associated with alignment. Varus knees showed significantly longer T2 in the superficial medial cartilage (ρ = –0.2, p = 0.04), and valgus knees in the lateral compartment (ρ = 0.1, p = 0.35). Associations were strongest for intra-articular malalignment (ρ = 0.3, p < 0.01). In constitutional varus, a non-significant medial T2 prolongation was observed (ρ = –0.2, p = 0.28); no changes were found in constitutional valgus. Conclusion: Lower limb malalignment, particularly intra-articular malalignment, is associated with compartment-specific lower cartilage quality, as reflected by longer T2 values. Distinguishing between bony and intra-articular malalignment, rather than overall limb alignment, should be a focus of future studies on malalignment. Future research should explore whether constitutional malalignment and early cartilage alterations may trigger cartilage degeneration and KOA progression.
CRIS-Team Scopus Importer:2025-10-31
Keywords: Intra-articular; Osteoarthritis; T2-mapping; Valgus malalignment; Varus malalignment